Metal organic framework material as well as preparation method, application and separation method thereof
By preparing a new metal organic frame material, the metal cation, N,N'-(1,4-phenylene)diisonicotinamide and organic ligand are combined by solvothermal reaction, the problem of existing MOFs not tolerant to moisture under humidity conditions is solved, and the efficient separation effect of CO2 under different humidity conditions is achieved.
Patent Information
- Application Number
- CN202311059841.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-22
AI Technical Summary
The existing metal organic frame materials (MOFs) are not wet resistant under humidity conditions and are difficult to meet the actual working conditions for efficient CO2 separation.
A new metal organic frame material is prepared by dissolving metal cations, N,N'-(1,4-phenylene)diisonicotinamide and organic ligand in an organic solvent at a specific molar ratio, and undergoing a solvothermal reaction, which has the properties of mild and moisture resistance.
The metal organic frame material can efficiently separate carbon dioxide and nitrogen under drying conditions or high humidity conditions, and has excellent thermal stability and moisture resistance to meet the needs of actual working conditions.
Smart Images

Figure CN119505255A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal organic framework material and a preparation method, application and separation method thereof, belonging to the technical field of gas adsorption and separation. Background Art
[0002] Metal-Organic Frameworks (MOFs) are a new type of microporous crystalline materials formed by self-assembly of organic ligands and metal ions. Metal ions or metal clusters act as nodes, and organic ligands act as bridges, often forming long-range ordered crystalline materials with regular pores. They are new materials that have developed rapidly in the field of coordination chemistry in recent decades. Compared with traditional inorganic porous materials, MOFs materials have excellent properties, such as highly ordered porous structure, high specific surface area, structural component adjustability, size and morphology controllability, functional diversity and good biocompatibility. Based on the above advantages, MOFs materials have been widely used in hydrogen storage, drug delivery, catalytic reactions, biosensors and other aspects. However, the current existing MOFs have very low stability, such as moisture resistance, and it is difficult to meet the high-efficiency CO2 separation process under actual working conditions. For example, although MOF materials such as Mg-MOF-74 (J.Am.Chem.Soc.2008,130,10870–10871) and SIFSIX-3-Zn (Nature2013,495,80–84) have good separation performance, they are not resistant to moisture and their structures will be destroyed when exposed to air or moisture, making it impossible to achieve CO2 separation under humid conditions.
[0003] Therefore, providing a new type of metal organic framework material and its preparation method, application and separation method has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a metal organic framework material.
[0005] Another object of the present invention is to provide a method for preparing the above metal organic framework material.
[0006] Another object of the present invention is to provide application of the above metal organic framework material in separation of carbon dioxide and nitrogen.
[0007] Another object of the present invention is to provide a method for separating carbon dioxide and nitrogen, wherein the adsorbent used is the metal organic framework material described above.
[0008] In order to achieve the above objectives, on the one hand, the present invention provides a metal organic framework material, wherein the metal organic framework material is prepared by dissolving metal cations, N,N'-(1,4-phenylene) diisonicotinamide and organic ligands in an organic solvent at a molar ratio of 1:0.1-2:0.1-2, preferably 1:1:1, and then subjecting the mixture to a solvothermal reaction.
[0009] The structural formula of the organic ligand is shown below:
[0010]
[0011] Wherein, R is one of H, CH3, NH2, F, Cl, Br, and OH;
[0012] The pores of the metal organic framework material contain amide groups and R groups.
[0013] As a specific embodiment of the metal-organic framework material described above in the present invention, the metal-organic framework material comprises two open channels, respectively denoted as channel A and channel B, wherein the length range of channel A is 1.1-1.4 nm, the width range is 0.3-0.5 nm, the length range of channel B is 0.4-0.7 nm, and the width range is 0.2-0.4 nm.
[0014] As a specific embodiment of the metal organic framework material described above in the present invention, the metal organic framework material has a temperature resistance of 250-350°C.
[0015] As a specific embodiment of the metal organic framework material described above in the present invention, wherein the metal cation comprises Cu 2+ 、Zn 2+ 、Co 2+ 、Ni 2+ and Mn 2+ Correspondingly, the metal cation can be provided by its corresponding metal salt, wherein the metal salt can be, for example, one or a combination of metal nitrate, sulfate, acetate and chloride.
[0016] As a specific embodiment of the metal organic framework material described above in the present invention, the temperature of the solvothermal reaction is 100-130° C., preferably 110-120° C., and the time is 4-72 h, preferably 24-48 h.
[0017] On the other hand, the present invention also provides a method for preparing the metal organic framework material described above, wherein the preparation method comprises:
[0018] Step 1: dissolving a metal cation, N,N'-(1,4-phenylene) diisonicotinamide and an organic ligand in an organic solvent at a molar ratio of 1:0.1-2:0.1-2 to obtain a mixed solution;
[0019] Step 2: heating the mixed solution to allow the metal cation, N,N'-(1,4-phenylene) diisonicotinamide and the organic ligand to undergo a solvothermal reaction, and after the reaction is completed, the metal organic framework material is obtained.
[0020] As a specific embodiment of the preparation method described above of the present invention, the organic solvent includes one or a combination of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), N-methylformamide (NMF) and dimethyl sulfoxide (DMSO).
[0021] In yet another aspect, the present invention further provides use of the metal organic framework material described above in separation of carbon dioxide and nitrogen.
[0022] In yet another aspect, the present invention further provides a method for separating carbon dioxide and nitrogen, wherein the adsorbent used in the separation method is the metal organic framework material described above.
[0023] As a specific embodiment of the separation method described above, the separation method is carried out under dry conditions or wet conditions. The present invention does not make specific requirements on the specific humidity of the wet conditions, that is, the separation method can be carried out under any humidity conditions. Preferably, the humidity of the wet conditions is not less than 75% RH.
[0024] As a specific embodiment of the separation method described above in the present invention, the adsorption temperature is -50 to 100°C, and the adsorption pressure does not exceed 50 bar.
[0025] As a specific embodiment of the separation method described above in the present invention, the desorption temperature is 25-150° C., and the carbon dioxide desorption pressure does not exceed 1.0 bar.
[0026] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:
[0027] The metal organic framework material provided by the present invention is a porous three-dimensional metal organic framework material, whose porosity is 25-35%, and contains two open channels, which are respectively recorded as channel A and channel B, wherein the length range of channel A is 1.1-1.4nm, the width range is 0.3-0.5nm, the length range of channel B is 0.4-0.7nm, the width range is 0.2-0.4nm, and the pore width of the open channels is not greater than 0.7nm, so the metal organic framework material has an ultra-microporous structure. The open channel size of the metal organic framework material is in line with the molecular dynamics diameter of CO2 (0.33nm), and when the metal organic framework material is used as an adsorbent to separate carbon dioxide and nitrogen, CO2 can enter the channel of the material, so that the metal organic framework material can achieve efficient separation of carbon dioxide and nitrogen; and the amide group and R group contained in the channel of the metal organic framework material also help to improve its specific separation performance for carbon dioxide.
[0028] In addition, the thermogravimetric test results show that the metal organic framework material adsorbent used in the present invention has a temperature resistance of 250°C-350°C, indicating that it has excellent thermal stability and can meet the thermal stability requirements of actual working conditions;
[0029] X-ray diffraction results show that the metal organic framework material used in the present invention is resistant to 75% RH moisture, water, and various corrosive organic solvents such as acetonitrile, N,N-dimethylformamide, methanol, etc. The reason is that: N,N'-(1,4-phenylene) diisonicotinamide and organic ligands have strong coordination ability with the metal cations used, and the metal cations in the metal organic framework material are all coordinated saturated. These two factors make the metal organic framework material have excellent thermal stability and moisture resistance and corrosion resistance. Organic solvent characteristics. Therefore, the metal organic framework material can achieve efficient separation of carbon dioxide and nitrogen under dry conditions or high humidity conditions, such as 75% RH moisture.
[0030] In summary, when the above-mentioned metal organic framework material is used as an adsorbent to separate carbon dioxide and nitrogen, its specific separation performance for carbon dioxide in the mixed gas can be significantly enhanced; and after adsorption, the regeneration conditions of the metal organic framework material are mild, it is easy to desorb and regenerate, and the regeneration process has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 The X-ray diffraction spectrum and powder X-ray diffraction refined spectrum of PRI-1-H-Cu provided in Example 1 of the present invention.
[0033] Figure 2 The X-ray diffraction spectrum and powder X-ray diffraction refined spectrum of PRI-1-H-Zn provided in Example 2 of the present invention.
[0034] Figure 3 The X-ray diffraction spectrum and powder X-ray diffraction refined spectrum of PRI-1-NH2-Cu provided in Example 3 of the present invention.
[0035] Figure 4 The X-ray diffraction spectrum and powder X-ray diffraction refined spectrum of PRI-1-NH2-Zn provided in Example 4 of the present invention.
[0036] Figure 5 This is the thermal stability curve of PRI-1-H-Cu provided in Example 1 of the present invention.
[0037] Figure 6 This is the thermal stability curve of PRI-1-H-Zn provided in Example 2 of the present invention.
[0038] Figure 7 This is the thermal stability curve of PRI-1-NH2-Cu provided in Example 3 of the present invention.
[0039] Figure 8 This is the thermal stability curve of PRI-1-NH2-Zn provided in Example 4 of the present invention.
[0040] Fig. 9 This is a powder X-ray diffraction spectrum of PRI-1-H-Cu provided in Example 1 of the present invention after being fully exposed to water, 75% humidity environment, N,N-dimethylformamide and acetonitrile.
[0041] Fig.10 This is the single-component adsorption isotherm of CO2 and N2 of PRI-1-H-Cu at 25°C provided in Example 1 of the present invention.
[0042] Fig.11 The single-component adsorption isotherms of CO2 and N2 of PRI-1-H-Zn at 25°C provided in Example 2 of the present invention.
[0043] Fig.12 The single-component adsorption isotherms of CO2 and N2 of PRI-1-NH2-Cu at 25°C provided in Example 3 of the present invention.
[0044] Fig.13The single-component adsorption isotherms of CO2 and N2 of PRI-1-NH2-Zn at 25°C provided in Example 4 of the present invention.
[0045] Fig.14 This is a graph showing the results of a penetration test of the PRI-1-H-Cu provided in Example 1 of the present invention on a dry 15v% CO2 / 85v% N2 mixed gas at a temperature of 25°C.
[0046] Fig.15 This is a graph showing the results of cyclic penetration of PRI-1-H-Cu provided in Example 1 of the present invention when it is purged and regenerated using an inert gas at 25°C and 1 bar.
[0047] Fig.16 This is a graph showing the results of a penetration test of the PRI-1-H-Cu provided in Example 1 of the present invention on a 15v% CO2 / 85v% N2 mixed gas with a relative humidity of 75% at a temperature of 25°C. DETAILED DESCRIPTION
[0048] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0049] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0050] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0051] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0052] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0053] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The embodiments described below are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially. For example, the reagents used in the embodiments of the present invention can be purchased from Sinopharm Reagents and Yanshen Technology Co., Ltd.
[0055] Metal-organic framework material examples
[0056] Example 1
[0057] This embodiment provides a three-dimensional porous copper organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0058] Dissolve 0.25 mmol N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol terephthalic acid and 0.25 mmol Cu(NO3)2·3H2O in 10 mL N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0059] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvent thermal reaction at 120°C for 48 hours;
[0060] Then, the product was filtered, washed, and activated at 100° C. in vacuum for 24 hours to obtain the three-dimensional porous copper organic framework material crystal, which was recorded as PRI-1-H-Cu.
[0061] Example 2
[0062] This embodiment provides a three-dimensional porous zinc organic framework material, wherein the three-dimensional porous zinc organic framework material is prepared by a preparation method comprising the following specific steps:
[0063] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of terephthalic acid and 0.25 mmol of Zn(NO3)2·6H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0064] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvent thermal reaction at 120°C for 48 hours;
[0065] Then, the product was filtered, washed, and activated at 100° C. in vacuum for 24 hours to obtain the three-dimensional porous zinc organic framework material crystal, which was recorded as PRI-1-H-Zn.
[0066] Example 3
[0067] This embodiment provides a three-dimensional porous copper organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0068] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of 2-aminoterephthalic acid and 0.25 mmol of Cu(NO3)2·3H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0069] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvent thermal reaction at 120°C for 36 hours;
[0070] Then, the three-dimensional porous copper organic framework material crystal was obtained by filtering, washing, and vacuum activation at 100° C. for 24 hours, and was recorded as PRI-1-NH2-Cu.
[0071] Example 4
[0072] This embodiment provides a three-dimensional porous zinc organic framework material, wherein the three-dimensional porous zinc organic framework material is prepared by a preparation method comprising the following specific steps:
[0073] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of 2-aminoterephthalic acid and 0.25 mmol of Zn(NO3)2·6H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0074] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvent thermal reaction at 120°C for 36 hours;
[0075] Then, the mixture was filtered, washed, and activated under vacuum at 100° C. for 24 hours to obtain the three-dimensional porous zinc organic framework material crystal, which was recorded as PRI-1-NH2-Zn.
[0076] Example 5
[0077] This embodiment provides a three-dimensional porous copper organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0078] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of 2-fluoroterephthalic acid and 0.25 mmol of Cu(NO3)2·3H2O in 10 mL of N,N-dimethylacetamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0079] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvothermal reaction at 120°C for 24 hours;
[0080] Then, the three-dimensional porous copper organic framework material crystal is obtained by filtering and washing, and is recorded as PRI-1-F-Cu.
[0081] Example 6
[0082] This embodiment provides a three-dimensional porous copper organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0083] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of 2-aminoterephthalic acid and 0.25 mmol of Cu(NO3)2·3H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0084] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvothermal reaction at 110°C for 36 hours;
[0085] Then, the three-dimensional porous copper organic framework material crystal was obtained by filtering, washing, and vacuum activation at 100° C. for 24 hours, and was recorded as PRI-1-NH2-Cu.
[0086] Example 7
[0087] This embodiment provides a three-dimensional porous nickel organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0088] Dissolve 0.5 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.5 mmol of terephthalic acid and 0.25 mmol of Ni(NO3)2·6H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0089] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvothermal reaction at 120°C for 24 hours;
[0090] Then, the three-dimensional porous copper organic framework material crystal is obtained by filtering and washing, and is recorded as PRI-1-H-Ni.
[0091] Example 8
[0092] This embodiment provides a three-dimensional porous cobalt organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0093] Dissolve 0.125 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.125 mmol of terephthalic acid and 0.25 mmol of Co(NO3)2·6H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0094] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvent thermal reaction at 100°C for 24 hours;
[0095] Then, the three-dimensional porous copper organic framework material crystal is obtained by filtering and washing, and is recorded as PRI-1-H-Co.
[0096] Example 9
[0097] This embodiment provides a three-dimensional porous manganese organic framework material, wherein the copper organic framework material is prepared by a preparation method comprising the following specific steps:
[0098] Dissolve 0.25 mmol of N,N'-(1,4-phenylene) diisonicotinamide, 0.25 mmol of terephthalic acid and 0.25 mmol of Mn(NO3)2·6H2O in 10 mL of N,N-dimethylformamide, stir at room temperature and dissolve by ultrasonication to obtain a reaction precursor solution;
[0099] Subsequently, the reaction precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the stainless steel reactor was sealed and placed in an oven for solvothermal reaction at 130°C for 24 hours;
[0100] Then, the three-dimensional porous copper organic framework material crystal is obtained by filtering and washing, and is recorded as PRI-1-H-Mn.
[0101] Characterization Test Example 1
[0102] In this characterization test example, a Bruker D2 PHASER diffractometer was used, and Cu Kα rays (λ=0.15406 nm) were used as the radiation source at room temperature to test the PRI-1-H-Cu provided in Example 1 and collect crystal X-ray diffraction data. The collected crystal X-ray diffraction data and the powder X-ray diffraction refinement pattern were then plotted in the same figure, as shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the X-ray powder diffraction pattern of the ultramicroporous material obtained in Example 1 is consistent with the powder X-ray diffraction refined pattern.
[0103] Characterization Test Example 2
[0104] In this characterization test example, a Bruker D2 PHASER diffractometer was used, and Cu Kα rays (λ=0.15406 nm) were used as the radiation source at room temperature to test the PRI-1-H-Zn provided in Example 2 and collect crystal X-ray diffraction data. The collected crystal X-ray diffraction data and the powder X-ray diffraction refinement pattern were then plotted in the same figure, as shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the X-ray powder diffraction pattern of the ultramicroporous material obtained in Example 2 is consistent with the powder X-ray diffraction refined pattern.
[0105] Characterization Test Example 3
[0106] In this characterization test example, a Bruker D2 PHASER diffractometer was used, and Cu Kα rays (λ=0.15406 nm) were used as the radiation source at room temperature to test the PRI-1-NH2-Cu provided in Example 3 and collect crystal X-ray diffraction data. The collected crystal X-ray diffraction data and the powder X-ray diffraction refinement pattern were then plotted in the same figure, as shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that the X-ray powder diffraction pattern of the ultramicroporous material obtained in Example 3 is consistent with the powder X-ray diffraction refined pattern.
[0107] Characterization Test Example 4
[0108] In this characterization test example, a Bruker D2 PHASER diffractometer was used, and Cu Kα rays (λ=0.15406 nm) were used as the radiation source at room temperature to test the PRI-1-NH2-Zn provided in Example 4 and collect crystal X-ray diffraction data. The collected crystal X-ray diffraction data and the powder X-ray diffraction refinement pattern were then plotted in the same figure, as shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that the X-ray powder diffraction pattern of the ultramicroporous material obtained in Example 4 is consistent with the powder X-ray diffraction refined pattern.
[0109] According to Figure 1-Figure 4 The results shown also show that the metal organic framework materials provided in Examples 1 to 4 of the present invention are porous three-dimensional metal organic framework materials with a porosity of 25-35%, comprising two open channels, respectively denoted as channel A and channel B, wherein channel A has a length range of 1.1-1.4 nm and a width range of 0.3-0.5 nm, and channel B has a length range of 0.4-0.7 nm and a width range of 0.2-0.4 nm. Since the pore widths of the open channels are all no greater than 0.7 nm, the metal organic framework material has an ultra-microporous structure. According to the experimental results of Examples 1 to 4, it can be reasonably predicted that the metal organic framework materials provided in Examples 5 to 9 of the present invention are also porous three-dimensional metal organic framework materials with a porosity of 25-35%, comprising two types of open channels, respectively denoted as channel A and channel B, wherein the length range of channel A is 1.1-1.4 nm, the width range is 0.3-0.5 nm, the length range of channel B is 0.4-0.7 nm, the width range is 0.2-0.4 nm, and it has an ultra-microporous structure.
[0110] Characterization Test Example 5
[0111] In this characterization test example, 12 mg of PRI-1-H-Cu was weighed and subjected to a thermal stability test using a thermogravimetric analyzer. The heating rate during the test was 5°C / min, and the test temperature range was from room temperature to 600°C. The measured thermal stability curve is shown in Figure 2. Figure 5 As shown. Figure 5 It can be seen that the PRI-1-H-Cu provided in Example 1 of the present invention can maintain good structural stability within 290°C.
[0112] Characterization Test Example 6
[0113] In this characterization test example, 13 mg of PRI-1-H-Zn was weighed and the thermal stability was tested using a thermogravimetric analyzer. The heating rate during the test was 5°C / min and the test temperature range was from room temperature to 600°C. The measured thermal stability curve is shown in the figure below: Figure 6 As shown. Figure 6 It can be seen that the PRI-1-H-Zn provided in Example 2 of the present invention can maintain good structural stability within 350°C.
[0114] Characterization Test Example 7
[0115] In this characterization test example, 12 mg of PRI-1-NH2-Cu was weighed and its thermal stability was tested using a thermogravimetric analyzer. The heating rate during the test was 5°C / min, and the test temperature range was from room temperature to 600°C. The measured thermal stability curve is shown in the figure below: Figure 7 As shown. Figure 7 It can be seen that the PRI-1-NH2-Cu provided in Example 3 of the present invention can maintain good structural stability within 270°C.
[0116] Characterization Test Case 8
[0117] In this characterization test example, 13 mg of PRI-1-NH2-Zn was weighed and the thermal stability was tested using a thermogravimetric analyzer. The heating rate during the test was 5°C / min and the test temperature range was from room temperature to 600°C. The measured thermal stability curve is shown in the figure below. Figure 8 As shown. Figure 8 It can be seen that the PRI-1-NH2-Zn provided in Example 4 of the present invention can maintain good structural stability within 340°C.
[0118] Characterization Test Case 9
[0119] In this characterization test example, 50 mg of PRI-1-H-Cu was first weighed into a plastic tube, and then a certain amount of water, acetonitrile, and N,N-dimethylformamide were added thereto respectively, and PRI-1-H-Cu was placed in a saturated sodium chloride solution (used to provide 75% relative humidity conditions) to allow the solid powder to fully contact with different solvents such as water, acetonitrile, N,N-dimethylformamide and saturated sodium chloride solution, and then allowed to stand at room temperature after shaking; after 24 hours, it was vacuum dried at 60°C to obtain PRI-1-H-Cu treated with different solvents.
[0120] The PRI-1-Cu material treated with different solvents was subjected to X-ray powder diffraction test, and the obtained spectrum was as follows: Fig. 9 As shown, from Fig. 9 It can be seen that PRI-1-Cu can maintain good XRD peak shape after being fully exposed to water, 75% RH environment, acetonitrile, and N,N-dimethylformamide, indicating that the material has excellent crystal phase stability.
[0121] Separation method example
[0122] Example 1-1
[0123] In this example, 100 mg of PRI-1-H-Cu was first weighed, and then a gravimetric gas adsorption instrument (conventional equipment) was used to heat and vacuum degas for 6 h at 100°C, and then the adsorption isotherms of single-component gases CO2 and N2 were tested at 25°C. The results are shown in FIG. Fig.10 shown. Fig.10 The data in show that the PRI-1-H-Cu provided in Example 1 of the present invention has a significant ability to preferentially adsorb CO2.
[0124] Example 2-2
[0125] In this example, 91 mg of PRI-1-H-Zn was first weighed, and then a gravimetric gas adsorption instrument (conventional equipment) was used to heat and vacuum degas for 6 h at 100°C, and then the adsorption isotherms of single-component gases CO2 and N2 were tested at 25°C. The results are shown in FIG. Fig.11 shown. Fig.11 The data in show that PRI-1-H-Zn provided in Example 2 of the present invention also has a significant ability to preferentially adsorb CO2.
[0126] Example 3-3
[0127] In this example, 110 mg of PRI-1-NH2-Cu was first weighed, and then a gravimetric gas adsorption instrument (conventional equipment) was used to heat and vacuum degas for 6 h at 100°C, and then the adsorption isotherms of single-component gases CO2 and N2 were tested successively at 25°C. The results are shown in FIG. Fig.12shown. Fig.12 The data in show that the PRI-1-NH2-Cu provided in Example 3 of the present invention also has a significant ability to preferentially adsorb CO2.
[0128] Example 4-4
[0129] In this example, 100 mg of PRI-1-NH2-Zn was first weighed, and then a gravimetric gas adsorption instrument (conventional equipment) was used to heat and vacuum degas for 6 h at 100°C, and then the adsorption isotherms of single-component gases CO2 and N2 were tested at 25°C. The results are shown in the figure. Fig.13 shown. Fig.13 The data in show that PRI-1-NH2-Zn provided in Example 4 of the present invention also has a significant ability to preferentially adsorb CO2.
[0130] Example 5-1
[0131] In this embodiment, the PRI-1-H-Cu powder sample provided in Example 1 of the present invention is first loaded into a gasket-type analytical column with a diameter of 4.6 mm and a length of 50 mm, and then connected to a He gas pipeline with a flow rate of about 20 sccm, and placed at a temperature of 100°C for purging and degassing overnight. The gasket-type analytical column loaded with the PRI-1-H-Cu powder sample is then placed in a gas phase permeation device for a permeation test. The specific test conditions are: the adsorption separation temperature is 25°C, the pressure is 1 bar, the test gas is 15v% CO2 / 85v% N2, and the flow rate is 2sccm.
[0132] The data measured in this embodiment are as follows Fig.14 As shown, from Fig.14 It can be seen that at the beginning of the test, N2 will pass through the sample immediately, while CO2 will not appear until about 30 min / g, and the time difference is as long as 30 min / g, indicating that the PRI-1-H-Cu material provided in Example 1 of the present invention can achieve efficient separation of 15v% CO2 / 85v% N2 under dry conditions.
[0133] Example 6-1
[0134] In this embodiment, the PRI-1-H-Cu powder sample provided in Example 1 of the present invention is first loaded into a gasket-type analytical column with a diameter of 4.6 mm and a length of 50 mm, and then connected to a He gas pipeline with a flow rate of about 20 sccm, and placed at a temperature of 100° C. for purging and degassing overnight. Then, the gasket-type analytical column loaded with the PRI-1-H-Cu powder sample is placed in a gas phase permeation device for permeation testing. The specific test conditions are: adsorption separation temperature is 25° C., pressure is 1 bar, test gas is 15v% CO2 / 85v% N2, and flow rate is 2sccm;
[0135] After the breakthrough, the sample was regenerated for 30 min at 25°C with a flow rate of 20 sccm He and a pressure of 1 bar, and then the 15v% CO2 / 85v% N2 mixed gas dynamic test was continued as shown above. This was repeated 5 times to obtain a cyclic breakthrough curve, as shown in FIG. Fig.15 As shown, from Fig.15 It can be seen that the sample can be easily regenerated by purging with inert gas at a temperature of 25°C, indicating that the regeneration conditions of the PRI-1-H-Cu material provided in Example 1 of the present invention are mild and the regeneration energy consumption is low.
[0136] Example 7-1
[0137] In this embodiment, the PRI-1-H-Cu powder sample provided in Example 1 of the present invention is first loaded into a gasket-type analytical column with a diameter of 4.6 mm and a length of 50 mm, and then connected to a He gas pipeline with a flow rate of about 20 sccm, and placed at a temperature of 100° C. for purging and degassing overnight. The gasket-type analytical column loaded with the PRI-1-H-Cu powder sample is then placed in a gas phase permeation device for a permeation test. The specific test conditions are: the adsorption separation temperature is 25° C., the pressure is 1 bar, the test gas is 15v% CO2 / 85v% N2 (75% relative humidity), and the flow rate is 2sccm.
[0138] The data measured in this embodiment are as follows Fig.16 As shown, Fig.16 The experimental data in show that the PRI-1-H-Cu material provided in Example 1 of the present invention can achieve efficient separation of 15v% CO2 / 85v% N2 under high humidity conditions of 75% RH.
[0139] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A metal organic framework material, characterized in that: The metal organic framework material is prepared by dissolving metal cations, N,N'-(1,4-phenylene) diisonicotinamide and organic ligands in an organic solvent at a molar ratio of 1:0.1-2:0.1-2 and then subjecting the mixture to a solvothermal reaction. The structural formula of the organic ligand is shown below: Wherein, R is one of H, CH3, NH2, F, Cl, Br, and OH; The pores of the metal organic framework material contain amide groups and R groups.
2. The metal organic framework material according to claim 1, characterized in that: The metal organic framework material comprises two open channels, which are respectively denoted as channel A and channel B, wherein the length range of channel A is 1.1-1.4 nm and the width range is 0.3-0.5 nm, and the length range of channel B is 0.4-0.7 nm and the width range is 0.2-0.4 nm.
3. The metal organic framework material according to claim 1, characterized in that: The metal organic framework material has a temperature resistance of 250-350°C.
4. The metal organic framework material according to any one of claims 1 to 3, characterized in that: The metal cations include Cu 2+ 、Zn 2+ 、Co 2+ 、Ni 2+ and Mn 2+ One or a combination of the following.
5. The metal organic framework material according to any one of claims 1 to 3, characterized in that: The temperature of the solvent thermal reaction is 100-130° C. and the time is 4-72 hours.
6. The method for preparing the metal organic framework material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step 1: dissolving a metal cation, N,N'-(1,4-phenylene) diisonicotinamide and an organic ligand in an organic solvent at a molar ratio of 1:0.1-2:0.1-2 to obtain a mixed solution; Step 2: heating the mixed solution to allow the metal cation, N,N'-(1,4-phenylene) diisonicotinamide and the organic ligand to undergo a solvothermal reaction, and after the reaction is completed, the metal organic framework material is obtained.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylformamide and dimethyl sulfoxide.
8. Use of the metal organic framework material according to any one of claims 1 to 5 in separating carbon dioxide and nitrogen.
9. A method for separating carbon dioxide and nitrogen, characterized in that: The adsorbent used in the separation method is the metal organic framework material according to any one of claims 1 to 5.
10. The separation method according to claim 9, characterized in that The conditions of the separation method are dry conditions or wet conditions.
11. The separation method according to claim 9 or 10, characterized in that: The adsorption temperature is between -50 and 100°C and the adsorption pressure does not exceed 50 bar.
12. The separation method according to claim 9 or 10, characterized in that: The desorption temperature is 25-150°C, and the carbon dioxide desorption pressure does not exceed 1.0 bar.
Citation Information
Patent Citations
Metal-organic framework material for efficient CO2 / N2 selective separation and adsorption and preparation method of metal-organic framework material
CN106588960A
Zinc-based metal organic framework material Zn-DPT-PTOBA as well as preparation method and application thereof
CN115894960A